(untitled) (Research, Society and Development, 2021)
Objective: to analyze the youth’s speeches produced in the Program “In Tuning with Health”, broadcast on web radio, about dialogues on hearing health. Methodology: descriptive and documentary research, with qualitative approach, covering the content of synchronous communication, from a group of 83 participants. Results: the youths demonstrate in their speeches that the knowledge of modern sciences make up their repertoire of knowledge and interests on the subject, as well as their sayings circulated around hygienic care, legal regulations with public and private sound, the proper uses of ear devices and illnesses caused by excessive noise. Conclusion: In view of this, dialogues mediated from web radio strengthened hearing health care, facilitated by the use of information accessed through digital communication devices, essential to health promotion.